Accountability of Zakat Institutions: Integrating Islamic Law and Maqāṣid al-sharī‘ah Perspectives in Fair Governance - Tambunan, Jannus; Harahap, Purnama Hidayah; Danil, Muhammad (As-Siyasi: Journal of Constitutional Law, 2026)
The management of zakat as an instrument of social justice in Islam requires accountability that is not only administrative, but also normative and substantive. In practice, the accountability of zakat management institutions is often understood narrowly as a duty of reporting and institutional compliance, thereby neglecting the theological dimensions and sharia objectives inherent in zakat. This article aims to reconstruct the concept of accountability of zakat management institutions from the perspective of Islamic law and Maqāṣid al-sharī‘ah. Using a conceptual-normative approach, this article analyzes the principles of amanah, accountability, and Islamic governance by placing Maqāṣid al-sharī‘ah as the substantive orientation of zakat management. This article analyzes Islamic Law doctrines and the principles of Maqāṣid al-sharī‘ah to reconstruct the framework of zakat institutional governance. Conducted as a literature-based qualitative study. This study successfully builds an integrated accountability model by synthesizing Islamic Law doctrines and the philosophy of Maqāṣid al-sharī‘ah, distinguishing itself from previous conventional concepts by shifting the paradigm from a one-dimensional focus, which has long been confined to financial compliance and administrative formalities, to a multidimensional framework that simultaneously embeds theological, social, and institutional aspects. This theoretical implication of literature on Sharia Governance by deconstructing secular accountability standards to better accommodate spiritual dimensions; meanwhile, its practical implication compels a transformation of key performance indicators of zakat institutions to move beyond mere financial audit opinions toward measuring real social justice impacts, while also serving as a compass for regulators to formulate welfare-based (maslahah) Sharia auditing standards